Analysis of Influencing Factors on the Value of Carbon Assets in China Under the Background of Double Carbon — Take the Pilot Carbon Emission Trading Program in Guangdong Province as an Example - Suifang Duan (Journal of World Economy, 2023)
In recent years, with the rapid development of the global industrial economy, carbon dioxide emissions, the greenhouse effect, and other environmental problems have become increasingly obvious, the development of a low-carbon economy has become the goal pursued by all countries in the world, carbon market trading has also emerged and developed. With the continuous development of the carbon market, carbon assets are playing an increasingly important role for enterprises, and the assessment of carbon assets has greater potential for development prospects. However, at this stage, there are few studies on the value of carbon assets in the field of assessment, and the studies on the influencing factors of the value of carbon assets are more focused on the analysis of the price of carbon emission rights. This paper takes carbon asset trading as the background and carbon emission trading pilot in Guangdong Province as an example and selects five indicators from different fields to establish a linear regression model to analyze the influencing factors of carbon emission rights price.